Oral and documentary history of the Darfur genocide Volume 2 - Samuel Totten; Totten, Samuel (Santa Barbara, Calif. : Praeger Security International, 2011)
An Oral and Documentary History of the Darfur Genocide presents the harrowing accounts of survivors and includes a collection of official documents delineating the international community's reaction to the Darfur crisis. In volume one, the survivors relate their experiences prior to, during, and following the genocidal events. Volume two is comprised of documents issued by the United States, the United Nations, and the ICC, each of which presents critical insights into how the international community has viewed and responded to the atrocities. The two-volume set is an invaluable record of the first genocidal act perpetrated in the 21st century. --Book Jacket.
6. Decision on the Prosecution's Application for a Warrant of Arrest against Omar Hassan Ahmad Al Bashir and Separate and Partly Dissenting Opinion of ICC Judge Anita Usacka, International Criminal Court, Public Redacted Version, March 4, 2009 -- 7. The Prosecutor's Appeal Regarding Dismissal of His Application for a Warrant of Arrest against Omar Hassan Ahmad Al Bashir, International Criminal Court, July 6, 2009 -- 8. Judgment on the Appeal of the Prosecutor against the Decision on the Prosecution's Application for a Warrant of Arrest against Omar Hassan Ahmad Al Bashir, International Criminal Court, February 3, 2010 -- 9. Second Warrant of Arrest against Omar Hassan Ahmad Al Bashir, International Criminal Court, July 12, 2010.
Includes bibliographical references and index.
Keywords: Refugees -- Sudan -- Darfur -- Interviews; Genocide -- Sudan -- Darfur; Genocide -- Sudan -- Darfur -- Sources; Ethnic conflict -- Sudan -- Darfur; Ethnic conflict -- Sudan -- Darfur -- Sources; Sudan -- History -- Darfur Conflict, 2003-; Sudan -- History -- Darfur Conflict, 2003- -- Sources